Autonomia terytorialna w europejskich krajach śródziemnomorskich - Kuchciak, Anna (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
In the European part of the Mediterranean Sea area there are countries which provide their territorial units with the constitutional guarantee of autonomy. The article briefly highlights the reasons for these institutional solutions and shows their current functioning. The considerations of the article are an attempt to locate specific national examples in the broader geographical context, ie. the Mediterranean region and its historical legacy.
Keywords: Mediterranean region; territorial autonomy; territorial system